Microbiological Assessment of Water Samples Collected from Different Areas of Karachi, Pakistan - Samiyah Tasleem (International Journal of Economic and Environmental Geology, 2018)
Water is essential for living beings. The strength of humans and different life forms is identified with safe water other than anything. The most well-known and far-reaching threat related to drinking water is pollution from direct and indirect resources straight forwardly or by implication, by sewage, different squanders or human excrement. Around 25 years back, legitimate evaluations showed that every year about 500 million individuals are influenced by water associated sickness and more than 10 million of these expire. In a current analysis in light of WHO information, it is shown that 3/4 of every single human sickness is caused by natural contamination. A total of 100 water samples were collected from different areas of Karachi for the microbiological assessment of contaminants in potable water. The samples were analyzed according to the standard microbiological testing protocol. Seventy-eight (78%) untreated and twenty-two (22%) treated water testers were found positive for coliforms. Fecal coliform and fecal Streptococci were present in 57 and 27 testers respectively. Escherichia coli were found in 73% of the samples which is an indicator of fecal contamination. Hence, we can use this study for microbiological assessment of the drinking water available in different areas of Karachi.